Genesis of enhanced photoactivity of CdS/Ni-x nanocomposites for visible-light-driven splitting of water - Devi, Suman; Korake, Prakash V.; Achary, Srungarpu N.; Gupta, Narencira M. (International Journal of Hydrogen Energy, 2014)
A series of CdS/Ni-x nanocomposite photocatalysts, containing ca. 0.6-15 wt% Ni, were synthesized using a one-step hydrothermal method and characterized for their crystallographic, morphological, interfacial, and optical properties. Rietveld refinement of powder XRD data revealed the coexistence of wurtzite (hexagonal) and zinc blende (cubic) phases of CdS in ratios dependent on Ni content. Only a fraction of Ni existed as a secondary phase of NiS while the majority occupied the lattice positions of hexagonal CdS. Whereas up to 10-fold enhancement in H-2 evolution compared with pure CdS was observed for samples containing similar to 1.5-4.5 wt% Ni, samples with smaller or larger Ni content displayed poor activity for visible-light-induced splitting of water in presence of sulfide-sulphite ions as sacrificial electron donors. In contrary to recent findings, our study reveals that the enhanced CdS photoactivity is not a result of charge transfer between p-type NiS and n-type CdS, Ni-induced visible-region absorbance, or the coating of CdS particles by non-photoactive NiS. Instead, the preparation-dependent hexagonal/cubic CdS phase boundaries and particle morphology may play a crucial role. Additionally, certain Ni-doping-induced sub-bandgap shallow energy levels contribute to charge carrier separation. Copyright (C) 2014, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: CdS/Ni-x nanocomposites; Dominant hexagonal facets; Enhanced photoactivity; Hydrogen evolution; Phase boundary effects; water splitting

Cadmium sulfide nanostructures: influence of morphology on the photocatalytic degradation of erioglaucine and hydrogen generation - Shenoy, Sulakshana; Jang, Eunyong; Park, Tae Joo; Gopinath, Chinnakonda S.; Sridharan, Kishore (Applied Surface Science, 2019)
Size and shape of inorganic materials are known to have great effects on their physical and chemical properties. Here, for the first time we report the visible light driven photocatalytic degradation of erioglaucine - a stable organic dye molecule in the presence of chemically synthesized nanoscale CdS with 1D (nanorods), 2D (nanosheets) and 3D (hierarchical) morphology. Visible light driven photocatalytic degradation efficiency of both 1D and 3D CdS in the removal of erioglaucine are identical. Surprisingly, with 5 min of sonication, the highly crystalline 3D CdS stacked with many thin nanowires containing numerous active surface sites exhibited fourfold enhanced photodegradation efficiency in comparison to 1D and 2D CdS. Scavenger studies revealed that electrons and superoxide radicals are primary reactive species involved in the photodegradation of erioglaucine, while cyclic photodegradation studies revealed the good stability of 3D CdS against photocorrosion. Further, the photocatalytic hydrogen evolution studies also revealed the excellent activity of 3D CdS in comparison to 1D and 2D CdS. Thus, we find that the morphology indeed influences the photocatalytic activity. These results reveal that 3D CdS nanostructures investigated in the present work are efficient photocatalysts that could be fine-tuned for both environmental remediation and hydrogen generation applications.
Keywords: Cadmium sulfide; Erioglaucine; Hydrogen evolution; Nanostructures; Photocatalysis

Direct thermal polymerization approach to N-rich holey carbon nitride nanosheets and their promising photocatalytic H-2 evolution and charge-storage activities - Antil, Bindu; Kumar, Lakshya; Reddy, K. P.; Gopinath, C. S.; Deka, Sasanka (ACS Sustainable Chemistry & Engineering, 2019)
Energy conversion and energy storage are two crucial challenges in green chemistry that have attracted tremendous attention for the last several decades. In this work, we have addressed both issues by synthesizing nitrogen-rich, few-layer-thick holey graphitic carbon nitride (g-C3N4) nanosheets by a simple, novel, direct thermal polymerization method, which is found to be very good in photocatalytic H-2 evolution reaction (energy-conversion) and charge-storage supercapacitor (energy-storage) applications. This as-synthesized conjugated polymer semiconductor (obtained stoichiometry C3N4.8) with unique structural and morphological advantages exhibits superior photocatalytic water splitting activity to H-2 evolution (2 620 mu mol h(-1) g(-1)) without the help of any cocatalysts under visible light in the presence of 20% triethanolamine (TEOA). The calculated apparent quantum yield is 8.5% at 427 nm, and the rate of photocatalytic hydrogen generation remained constant for nine consecutive catalytic cycles (9 h photocatalysis). The present material also shows electrochemical double layer capacitor (EDLC) behavior in alkaline electrolyte, where a symmetric coin cell device consisting of this electrode material without any large area support or conductive filler delivers high specific capacitance (275 F g(-1)), energy density (30 Wh kg(-1)), and power density (6651 W kg(-1)), and the supercapacitor cell can retain >98% capacitance efficiency up to 10 000 measured cycles at various current densities.
Keywords: g-C3N4; Hydrogen evolution; nanosheets; Photocatalyst; supercapacitor; water splitting

Hierarchical nanoflower arrays of Co9S8-Ni3S2 on nickel foam: a highly efficient binder-free electrocatalyst for overall water splitting - Illathvalappil, Rajith; Walko, Priyanka S.; Kanheerampockil, Fayis; Bhat, Suresh K.; Devi, R. Nandini; Kurungot, Sreekumar (Chemistry-A European Journal, 2020)
Hydrogen production is vital for meeting future energy demands and managing environmental sustainability. Electrolysis of water is considered as the suitable method for H-2 generation in a carbon-free pathway. Herein, the synthesis of highly efficient Co9S8-Ni3S2 based hierarchical nanoflower arrays on nickel foam (NF) is explored through the one-pot hydrothermal method (Co9S8-Ni3S2/NF) for overall water splitting applications. The nanoflower arrays are self-supported on the NF without any binder, possessing the required porosity and structural characteristics. The obtained Co9S8-Ni3S2/NF displays high hydrogen evolution reaction (HER), as well as oxygen evolution reaction (OER), activities in 1 m KOH solution. The overpotentials exhibited by this system at 25 mA cm(-2) are nearly 277 and 102 mV for HER and OER, respectively, in 1 m KOH solution. Subsequently, the overall water splitting was performed in 1 m KOH solution by employing Co9S8-Ni3S2/NF as both the anode and cathode, where the system required only 1.49, 1.60, and 1.69 V to deliver the current densities of 10, 25, and 50 mA cm(-2), respectively. Comparison of the activity of Co9S8-Ni3S2/NF with the state-of-the-art Pt/C and RuO2 coated on NF displays an enhanced performance for Co9S8-Ni3S2/NF both in the half-cell as well as in the full cell, emphasizing the significance of the present work. The post analysis of the material after water electrolysis confirms that the surface Co(OH)(2) formed during the course of the reaction serves as the favorable active sites. Overall, the activity modulation achieved in the present case is attributed to the presence of the open-pore morphology of the as formed nanoflowers of Co9S8-Ni3S2 on NF and the simultaneous presence of the surface Co(OH)(2) along with the highly conducting Co9S8-Ni3S2 core, which facilitates the adsorption of the reactants and subsequently its conversion into the gaseous products during water electrolysis.
Keywords: cobalt sulfide; electrocatalysts; Hydrogen evolution; overall water splitting; oxygen evolution

Hydrogen evolution via photocatalytic reforming of biomass with palladium nanoparticles decorated g-C3N4 nanosheets - Thara, Chinnu R.; Walko, Priyanka S.; Mathew, Beena (Renewable Energy, 2024)
Fossil fuel depletion and environmental toxins have made photocatalytic H2 production of paramount significance. A novel and unique technique for producing sustainable H2 and valorizing biomass using infinite solar energy is biomass photoreformation. Nevertheless, this environmentally friendly method is usually linked to severe reaction circumstances, insufficient selectivity, and restricted biomass conversion. Here, we present a novel one-pot photoreformation technique over porous g-C3N4 nanosheets surface-modified with Pd nano- particles to convert D-glucose to H2. By stacking the g-C3N4 photocatalyst into a 2D nanosheet structure, some of its inherent drawbacks can be mitigated. Furthermore, the inclusion of noble metal nanoparticles in these g-C3N4 nanosheet structures could significantly boost existing photocatalytic activity. The majority of solar radiation is composed of visible light, which makes up 45% of it, and ultraviolet light, which makes up 5%. Therefore, our focus has been on utilizing abundant visible light to facilitate biomass reformation. After 4 h of continuous irradiation, our composite photocatalyst exhibited exceptional visible light activity; its H2 evolution was 1839.84 mu molg- 1h- 1 , or about 27 times higher than that of undoped g-C3N4 nanosheets. The effectiveness of three different Pd loadings on g-C3N4 nanosheets for glucose reforming was examined. In the quest for an improved H2 evolution visible light active photocatalyst, g-C3N4 nanosheets made at various pyrolysis temperatures loaded with optimized Pd weight percentage were also examined.
Keywords: Biomass; D -glucose; g-C 3 N 4 nanosheets; Hydrogen evolution; palladium nanoparticles; Photocatalytic reforming